TURBINE GENERATOR LABORATORY MODEL TESTS TO DAMP TORSIONAL OSCILLATIONS WITH SUPPLEMENTARY SIGNALS - Sokhey, I; Limebeer, D; Macdonald, D (1993)
The improvement of generator stability by the use of supplementary signals into the voltage regulator and governor loops using discrete-time linear optimal control theory has been studied in this paper with particular emphasis on providing better damping for torsional oscillations. A multi-inertia laboratory model equipped with data acquisition and control computers was constructed to model the shaft dynamics of a 660 MW Drax turbine- generator. It is shown that the shaft torsional phenomena can be adequately simulated on a micro synchronous-generator at least as far as the dominant shaft torsional modes of vibration are concerned. The practical implementation of multi-mode LQG controllers has been shown to enhance system stability and provide better damping to the lower frequency torsional modes, which are those most susceptible to excitation.